Pengimplementasian Pendidikan Karakter Mengenai Kepedulian Lingkungan Pada Sekolah Sungai Di Gunung Anyar - Farhan Nauval Zulkarnain; G. Oka Warmana (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Character education is important for every individual, especially in terms of environmental awareness. Good character can be formed through education at school. Caring about the environment is important because it will have many positive impacts on every individual. To make this happen, it can be done by instilling various character values in students from an early age. This study aims to strengthen understanding of the importance of protecting the surrounding environment, especially for students at the River School, Gunung Anyar, Surabaya. This study uses conventional learning methods, question and answer methods and technology-based learning methods. In fact, this school has slowly shaped the students' character regarding caring for the environment. It is known that students are able to understand how to protect the environment.